The Portuguese Adaptation of the Mental Health Continuum-Short Form for Adult Population - Fonte, C (2020)
The Mental Health Continuum-Short Form (MHC-SF) is a self-report questionnaire that allows the assessment of positive mental health, including three well-being components—emotional, psychological and social—as well as the categorical diagnosis of the presence or absence of mental health. The purpose of this study is to describe the adaptation and validation of the Portuguese version of MHC-SF and to examine whether this is an adequate measure of positive mental health for the Portuguese context. The participants included 1448 respondents between the ages of 18 and 94 (M = 33.15; SD = 16.3), 70.1% of which were females. Results confirm the reliability (α = .93), tripartite factor structure, and the external and internal validity of the MHC-SF. Data also supported the two-continuum model, with positive mental health and mental illness belonging to two correlated but distinct dimensions. These findings indicated that the Portuguese MHC-SF is valid instrument to measure well-being and positive mental health.